REVIEW STUDY OF WESTERN WORLD LIFESTYLE FROM THE AYURVEDIC PERSPECTIVE - Patil, Jayashree; Shaikh, Nisar R (International Journal of Research -GRANTHAALAYAH, 2020)
This is for us to look at the western lifestyle through the lenses of ayurveda and it’s revived modified forms in today’s world. We are seeing the world from a totally different perspective where modern world has its roots to the start, changes needs changes to fulfill each other’s needs. And for human’s survival has always been the first priority to attend to. Western lifestyle is necessarily an adaptation of ayurvedic principles and this very thought gives support to the claim of universal ayurveda.